Strategi Komunikasi Politik Pemilu Legislatif menurut Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum di Provinsi Kalimantan Timur - Murni, Murni; Supriyadi, Supriyadi (Postgraduate University of Merdeka Malang, 2023)
This article examines and analyzes political communication strategies in legislative elections in East Kalimantan province using an ethnicity approach and the implementation of the Legislative election system according to Law Number 7 of 2017 concerning general elections. The research method used is the normative legal research method. The results of this research show that the communication strategy implemented by the legislative branch has been successful in its main form, generally in its form, namely focusing on the aspects of communication, mediation, competition/issue, and khailaiyaik saisairain. This fulfills the four components of kaimpaiye communication, namely; communicator, competitor, mediation of audience data. The factors that influence the success of the legislative pair's success include the ability to self-image, the player's ability to socialize with family/friends, the support group, the availability of the campaign, the performance of the legislative election and the success of the candidate's election. Furthermore, the implementation of Law Number 7 of 2017 in the 2019 elections in East Kalimantan, especially Samarinda City, the election organizers have implemented it in accordance with the Election Law.